Monday
March 27, 2017

Post a New Question

Posted by on .

Elimination using addition and subtraction:
1.
x - y = 1
x + y = 3

2.
-x + y = 1
x + y = 11

3.
x + 4y = 11
x - 6y = 11

4.
-x + 3y = 6
x + 3y = 18

PLEASE HELP!!!!
I NEED HELP ASAP!!!!

  • Algebra :\ - ,

    Either add or subtract one equation from the other to eliminate x.

    For example. ADD the two equations in Problem 1. This results in 2x = 4, which requires that x = 2. Use either equation to get y.

    You can certainly do the others yourself.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question